Case Report: Ninjin'yoeito May Improve Quality of Life After Hospitalization for Acute Illness in Patients With Frailty - Kashima, Masayuki (Frontiers in Nutrition, 2021)
Introduction: It is known that frail patients have a large number of diseases, and especially, frailty develops after acute illness. None of conventional drugs prevents exacerbation after acute illness. However, there are drugs in Kampo, which is traditional Japanese medicine, which are thought to have efficacy supplement energy and nutrition, and improving exhaustion after acute illness. Nijinyoeito is a representable drug of these Kampo’s drugs. Case: There are three cases of taken nijin’yoeito with frailty after acute illness. 87-year old male was admitted to our hospital caused by acute prostatitis complicated with hypertension and chronic obstructive pulmonary disease (COPD). He started taking ninjinyoeito from the date of discharge, the SF-36 which is total quality of life (QOL) score and has 8 components improved at 4 weeks and 12 weeks after discharge. Especially, body pain(BP41→51→100), social function(SF50→100→100) and mental health （MH75→75→90）were consistently improved. 65-year old male was admitted to our hospital caused by urinary tract infection complicated with primary sclerosing cholangitis and COPD. He started taking ninjin’yoeito from the date of discharge, the SF-36 all components physical function(PF70→95), role physical(RP75→100),body pain(BP72→84),general health(GH45→52), vitality(VT37.5→75), SF75→100, role emotional(RE75→100),MH(70→90) improved at 12 weeks after discharge. 80-year old male was admitted to our hospital caused by pneumonia complicated with hypertension. He started taking ninjin’yoeito from the date of discharge, the SF-36 was improved in RP(68.8→100), BP(52→61), GH(52→72), VT(43.8→62.5), SF(37.5→100) and RE(58.3→91.7) at 4 weeks after discharge. Discussion: In patients with frailty, SF-36 is often worsened after discharge of acute illness, but it is improved in patients who are taking ninjin’yoeito.